Da iniciativa do terceiro setor à implementação de uma política pública de saúde: um estudo de caso da Unidade Básica de Saúde Fluvial Abaré - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Introduction: This study investigates the transformation journey of the Abaré Riverine Basic Health Unit (UBSF), initially a third-sector initiative, into a public health policy integrated into Brazil's Unified Health System (SUS). Focusing on riverine communities in Santarém, Belterra, and Aveiro, Pará, the study addresses the challenges, opportunities, and impacts of this transition, analyzing its contributions to improving management and effectiveness in health services within remote areas of the Amazon. Methodology: A descriptive and exploratory approach was adopted, based on literature review, document analysis, and interviews with Abaré UBSF managers. The study employed a case study method to understand the integration of the UBSF into the SUS, taking into account regional specificities and dynamics between the public and private sectors. Results: The findings indicate that integrating the Abaré UBSF into the SUS brought significant improvements in healthcare access for riverine communities, strengthening administrative management and intersectoral coordination. However, financial sustainability and adaptation to local particularities remain key challenges. The inclusion of teaching and research activities has also broadened Abaré's impact, fostering the development of new professionals trained to work in hard-to-reach areas. Conclusion: The study reinforces the importance of partnerships between the third sector and public authorities for formulating effective health policies in remote regions, such as the Amazon. The relevance of the Abaré UBSF is highlighted in safeguarding the right to health and promoting equity, contributing to expanded access to essential services and improved quality of life within the communities served.
Keywords: Saúde Pública; Unidade Básica de Saúde Fluvial; Políticas de Saúde; Amazônia.; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS